Using business process modelling to examine academic library activities for periodicals - Tbaishat, Dina (Library management, 2010)
Purpose - The paper's purpose is to examine the process for the acquisition of print and electronic periodicals acquisition process in academic libraries using a business process modelling technique, role activity diagram (RAD).Design methodology approach - A literature review examined process modelling in academic libraries. Multiple methods were used for data collection, including documentary analysis, and interviews (n=8) with library staff (mostly recorded) provided other details about the library processes. Two sites were studied. Direct observation was used occasionally as a less formal method. RAD was used as a modelling technique; this is part of the Riva business process-modelling suite (Ould).Findings - The role activity diagram examples illustrate the differences in processes between the sites and the paper explores how they were used to discuss comparisons and possible improvements with the library staff. In many ways this is a type of action research study, as discussions with the research participants and ongoing evaluations are integral to the research.Research limitations implications - This work is limited to one process in academic libraries; periodical acquisitions. It is also limited to two cases, although these are two contrasting sites, one in the UK and the other in Jordan.Practical implications - The modelling technique used was feasible, and provides a basis for improvement and management by supporting the analysis of process performance and behaviour.Originality value - A particular important aspect in bridging the gap between research and practice is communication, through presentation of information in a structured way - the pictorial representation in the business process analysis is used to assist in discussions between researchers and practitioners.